2011
DOI: 10.1167/iovs.10-5657
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Collagen Lamellae in the Anterior Stroma of the Human Cornea Visualized by Second Harmonic Generation Imaging Microscopy

Abstract: Collagen lamellae in the anterior stroma of the normal human cornea are interwoven in three dimensions and adhere densely to Bowman's layer. This structure may contribute to the rigidity and curvature of the anterior portion of the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 21 publications
5
54
0
Order By: Relevance
“…2629 Other studies have examined corneal tissue independently in its native state 3036 and in keratoconus 37,38 as well as following photochemical crosslinking (as discussed below). The results of these studies indicate that the corneal signal is optimized in the forward scattered direction, which makes sense given the cornea's transparency and the fact that light passes through the tissue to strike a monitor in forward scattered systems.…”
Section: Discussionmentioning
confidence: 99%
“…2629 Other studies have examined corneal tissue independently in its native state 3036 and in keratoconus 37,38 as well as following photochemical crosslinking (as discussed below). The results of these studies indicate that the corneal signal is optimized in the forward scattered direction, which makes sense given the cornea's transparency and the fact that light passes through the tissue to strike a monitor in forward scattered systems.…”
Section: Discussionmentioning
confidence: 99%
“…This expression represents an average over the whole stroma. Anterior collagen fibrils are more strongly interwoven compared to posterior fibrils (Morishige et al, 2011) and may exhibit different swelling behavior. In the constant-mass coordinate system, Darcy’s law becomes JV=Kμtrue[normaldPnormaldHwtrue]true[normaldξnormaldxfalse]normaldHwnormaldξ where the first bracketed term on the right follows from Eq. (A7) and the second follows from Eq.…”
Section: A1 Swelling Coordinate ξmentioning
confidence: 99%
“…This expression represents an average over the whole stroma. Anterior collagen fibrils are more strongly interwoven compared to posterior fibrils (Morishige et al, 2011) and may exhibit different swelling behavior.…”
Section: A1 Swelling Coordinate ξmentioning
confidence: 99%
“…The applications of these 2D techniques have shown potential in providing orientation distribution information to assess collagenous tissues and understand interactions between cells and the ECM. Nevertheless, we expect that 3D analysis represents more accurately the architecture of collagen fibers than 2D analysis, and may be more sensitive to subtle changes in the micro-environment [18]. For example, recent research on collagenous fibrosis has shown that 3D analysis depicts pathological changes due to fibrosis progression more precisely than 2D analysis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%